Mapping the product range of interdental brushes: sizes, shapes, and forces - Sekundo, Caroline; Staehle, Hans Jörg (Oral health & preventive dentistry, 2020)
Purpose: Preventive dentistry aims to improve oral hygiene, including the use of interdental cleansing aids. Clear and simple classifications may positively impact patient communication and motivate oral health behaviour. To date, there is no comparative analysis of interdental brush classifications and sizes. Materials and Methods: A total of 2320 interdental brush samples by 24 manufacturers was examined regarding their passage hole diameter (PHD) according to the ISO standard for interdental brushes (ISO16409:2016), and their current classifications were evaluated. Inter- and intrarater reliability of the ISO size classification were determined based on 20 raters and 10 interdental brushes. The insertion force for these interdental brushes was analysed in vitro. Results: Excellent intra- and interrater reliability was achieved (intraclass correlation coefficient (ICC) >= 0.973) overall, although greater variance was observed for bigger brush sizes. Insertion forces varied depending on size and form of the brushes, amounting to 1.58 N (SD = 1.27 N) for cylindric and tapered brushes, and to 2.31 N (SD = 0.81 N) for waist-shaped brushes. The size range of commercially available products was 0.6-5.2 mm PHD, 90% presenting with a PHD <= 2.0 mm. Size intervals were unsystematic. The ISO size was indicated by 33% of all manufacturers, the exact PHD by 25%. Conclusions: The determination of the PHD is a reproducible instrument for most brushes currently on the market. In vitro, forces developed based on this classification are mostly moderate, thus unlikely to cause periodontal trauma. Given the discontinuous range and unclear labelling of available products, the development of a simplified classification system by usage of the PHD may benefit the practitioner and patient alike by contributing to improve oral hygiene behaviours.
Gesehen am 23.07.2020